Crushing behavior of multi-cell tubes with a novel pattern of design for their cross-section under multiple crushing angles. Issue 28 (16th December 2022) - Pirmohammad, Sadjad; Ghahremanzadeh, Zahra
Abstract: Crushing behavior of multi-cell tubes with a novel pattern of design for their cross-section is investigated under axial and oblique loads. The tubes have hexagonal, octagonal and decagonal shapes. According to SAW method, the tubes of H-1, O-1 and D-1 show better crushing performance, and the decagonal tube of D-1 is found as the best energy absorber. Multi-objective optimization design of the D-1 is finally provided using NSGA-II and RBF metamodels. The optimal decagonal tube provides on average of 248% and 61% higher SEA and CFE, respectively, compared to the D-0. However, it offers 11% higher PCF than the D-0.